The associations of multimorbidity with the sum of annual medical and long-term care expenditures in Japan - Mori, Takahiro (BMC Geriatr, 2019)
BACKGROUND: The occurrence of multimorbidity (i.e., the coexistence of multiple chronic diseases) increases with age in older adults and is a growing concern worldwide. Multimorbidity has been reported to be a driving factor in the increase of medical expenditures in OECD countries. However, to the best of our knowledge, there is no published research that has examined the associations between multimorbidity and either long-term care (LTC) expenditure or the sum of medical and LTC expenditures worldwide. We, therefore, aimed to examine the associations of multimorbidity with the sum of medical and LTC expenditures for older adults in Japan. METHODS: Medical insurance claims data for adults ≥75 years were merged with LTC insurance claims data from Kashiwa city, a suburb in the Tokyo metropolitan area, for the period between April 2012 and September 2013 to obtain an estimate of medical and LTC expenditures. We also calculated the 2011 updated and reweighted version of the Charlson Comorbidity Index (CCI) scores. Then, we performed multiple generalized linear regressions to examine the associations of CCI scores (0, 1, 2, 3, 4, or ≥ 5) with the sum of annual medical and LTC expenditures, adjusting for age, sex, and household income level. RESULTS: The mean sum of annual medical and LTC expenditures was ¥1,086,000 (US$12,340; n = 30,042). Medical and LTC expenditures accounted for 66 and 34% of the sum, respectively. Every increase in one unit of the CCI scores was associated with a ¥257,000 (US$2920); 95% Confidence Interval: ¥242,000, 271,000 (US$2750, 3080) increase in the sum of the expenditures (p < 0.001; n = 29,915). CONCLUSIONS: Using a merged medical and LTC claims dataset, we found that greater CCI scores were associated with a higher sum of annual medical and LTC expenditures for older adults. To the best of our knowledge, this is the first study to examine the associations of multimorbidity with LTC expenditures or the sum of medical and LTC expenditures worldwide. Our study indicated that the economic burden on society caused by multimorbidity could be better evaluated by the sum of medical and LTC expenditures, rather than medical expenditures alone. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12877-019-1057-7) contains supplementary material, which is available to authorized users.